Smart City Development Models: A Cross-Cultural Regional Analysis - Sari Dewi, Kurnia (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This study aims to prove that the Smart City development model using a regional cross-cultural approach can develop a city into a smart city in accordance with the regional development program that has been determined.This study uses a qualitative approach. 3 (three) agencies implementing the smart city program are random sampling in this study And the research results will show the effectiveness of the smart city development model.